Idiosyncratic Risk, Borrowing Constraints and Financial Integration - A Discussion of Ambiguous Results - Alexander Wulff; Maik Heinemann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper examines the effects of financial market imperfections in the context of financial integration. We employ a general equilibrium model with heterogeneous entrepreneurs and address the question of cross-border capital flows from poor to rich as well as focus on aggregate capital accumulation, output and welfare. The motivation is based on the mixed results from the existing literature. We add to this debate by discussing the effects from a general perspective in an environment where entrepreneurs face capital risk, earn risky profits and receive riskless wage income. Moreover, borrowing constraints hinder consumption smoothing as well as restrict the access to external funds for scaling up individual production. In order to separate the distinct effects, we consider several scenarios. In the first scenario without binding borrowing constraints and no persistent effects of shocks, we overcome the restriction that no analytical solution is available by deriving two rules of thumb, predicting the outcome of the model with high accuracy. These rules explain under which condition the less financially developed country features lower levels of capital and output in the autarchic steady state, implying capital flows from poor to rich, as well as under which condition an increase in the interest rate implied by financial integration unambiguously leads to larger levels of capital and output in the integrated steady state. For plausible parametrizations, we find that both conditions are likely to hold. In the next steps, we add tight borrowing constraints and increase the persistence of shocks. Both changes strongly affect the results derived in the first scenario.
Keywords: F41; G11; D52; 330